2nd Annual Fresno County Young Lawyers Association Justice George Hopper Luncheon - Watkins, Howard::::::::: (1983)
Herbert Levy, California Supreme Court Associate Justice Frank Richardson, Stephen Kane At entrance to Champagne Ballroom--Golden State Plaza